Agitated Saline Contrast Echocardiogram In Cardio-Pulmonary Evaluation - Hirachan, Anish; Sharma, Ranjit; Neupane, Prabesh (Nepalese Heart Journal, 2021)
Agitated saline contrast echocardiogram (ASC) is a very useful technique to detect various intracardiac and extra cardiac shunts in daily cardiology practice . Conventional 2D and color echocardiogram may not be well effective in ruling out various intracardiac shunts especially with patients having poor echo window. The introduction of agitated saline with bubbles formed during the study can help delineate different right to left shunt physiology commonly like patent foramen ovale (PFO) which is often sought for in evaluation of cases with young stroke . Various other etiologies like atrial septal defects, atrial septal aneurysm, large right to left shunts with eisenmengerisation can also be evaluated with this simple bedside study.